HUBUNGAN LAMA KERJA PERAWAT DENGAN KEPUASAN PASIEN PASCA BEDAH DI RUANG PERAWATAN BEDAH RS PKU MUHAMMADIYAH GOMBONG - timbul prayitno; saryono -; sarwono - (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2011)
Currently, nursing care services have been changing dramatically in Indonesia, especially when giving nursing care services at hospital and community. Previously, nursing care services emphasized giving nursing procedure rather than nursing care that practicing problem solving method based on nursing process and nursing science. This situation will force nurses to work harder than previously This research is to find out the correlation between nurse’s job period with post operation patients’ satisfaction in surgery care room of PKU Muhammadiyah Gombong Hospital. It was an analytical research that used cross sectional method. There were 87 respondents used as the samples research. The variables were nurse’s job period as independent variable and post operation patients satisfaction as the dependent variable. The instrument used was questioner. The data were analyzed by using spearman Rho correlation. The finding showed that there was correlation between nurse’s job period with post operation patients’ satisfaction in surgery care room of PKU Muhammadiyah Gombong Hospital with coefficient correlation result = 0.810 by seeing the probability sig value 0.001<0.005. it can be concluded that there is correlation between nurse’s job period with in surgery care room of PKU Muhammadiyah Gombong Hospital. Keywords: nurse’s job period, post operation patients’ satisfaction.